Performance comparison of numerical integration methods for solving complicated integration problems / Wan Ariesha Farhah Wan Asri & Nur Hazwani Dahnan - Wan Asri, Wan Ariesha Farhah; Dahnan, Nur Hazwani (2019)
Solving integration problems is very important as it is commonly appeared in wide range of fields and profession such as physics, mathematics and engineering. There are four known theoretical methods used to solve integration problems which are integration by substitution, integration by trigonometric substitution, integration by partial fraction and integration by part. However, these theoretical methods are quite complicated and leads to long and laborious calculation. Therefore, researchers tend to use numerical method which is quite simple and easy. In this project, seven numerical methods that are Trapezoidal Rule, Simpson’s 1/3 Rule, Simpson’s 3/8 Rule, Boole’s Rule, Weddle’s Rule, Durand’s Rule and Hardy’s Rule are chosen to solve complicated integration problems. The error is analyzed using percentage error of both exact and approximate value. The main purpose of this study is to determine the best numerical methods for solving integration problems.